2010
DOI: 10.2174/1874192401004010001
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Passive Opium Smoking on Cardiovascular Indices of Rabbits with Normal and Ischemic Hearts

Abstract: Some Asian people believe that opium can protect the cardiovascular system. To assess this belief, we investigated the effect of passive opium smoking (POS) on cardiovascular indices in rabbits with ischemic and non-ischemic hearts.Rabbits (n = 43) were divided into control (CTL), short term opium (SO) and long term opium (LO) groups. SO and LO groups were exposed to opium smoking for 3 days and 4 weeks, respectively. ECG, blood pressure (BP), left ventricular pressure and cardiac troponin I levels were record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
(15 reference statements)
1
20
0
Order By: Relevance
“…Regarding the effect of cigarette smoking and opium consumption, the results of this study showed almost no statistically significant effects on control of diabetes or odds ratio of predictors of diabetes (Tables 2,3). However, based on the effect on some other risk factors such as the increase in basal mean arterial pressure and low-density lipoprotein/high-density lipoprotein (LDL/ HDL) ratio, 24 increase in prevalence of high systolic blood pressure and reduction in HDL, 25 and more ECG abnormalities found in long term opium exposure, 26 the findings are in contrast to the belief of many opium consumers in Iran that opium may have an ameliorating effect on diabetes or other CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the effect of cigarette smoking and opium consumption, the results of this study showed almost no statistically significant effects on control of diabetes or odds ratio of predictors of diabetes (Tables 2,3). However, based on the effect on some other risk factors such as the increase in basal mean arterial pressure and low-density lipoprotein/high-density lipoprotein (LDL/ HDL) ratio, 24 increase in prevalence of high systolic blood pressure and reduction in HDL, 25 and more ECG abnormalities found in long term opium exposure, 26 the findings are in contrast to the belief of many opium consumers in Iran that opium may have an ameliorating effect on diabetes or other CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the beta cells and desensitization of insulin receptor signalling by opiates have been posited as potential mechanisms . In addition to their effects in causing metabolic dysregulation, recent studies in men have also implicated opioid use as a risk factor for coronary artery disease . Whether this effect of opiates is a direct effect on the arterial wall or via their influence on metabolic and inflammatory mediators remains unclear and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…26,29 In addition to their effects in causing metabolic dysregulation, recent studies in men have also implicated opioid use as a risk factor for coronary artery disease. 21,30,31 Whether this effect of opiates is a direct effect on the arterial wall or via their influence on À0Á04 (À0Á06, À0Á01) 0Á003 À0Á01 (À0Á02, À0Á03) 0Á01 Fasting glucose À0Á05 (À1Á3, 1Á2) 0Á93 0Á01 (À0Á4, 0Á43) 0Á94 Fasting insulin À0Á01 (À0Á7, 0Á8) 0Á97 À0Á03 (À0Á31, 0Á25) 0Á83…”
Section: Discussionmentioning
confidence: 99%
“…A polyethylene cannula containing saline-heparin solution (15 l/mL) was inserted into the isolated right carotid artery and then was connected to a pressure transducer to measure the arterial blood pressure (Joukar et al, 2010). The mean arterial pressure (MAP) was calculated by ''MAP ¼ Pd + (PsÀPd)/3 formula'', in which Pd is the diastolic arterial pressure and Ps is the systolic arterial pressure.…”
Section: Hemodynamic Measurementsmentioning
confidence: 99%